Politics based on a Biblical Perspective and its Implications for the Involvement of Believers in Politics - Salomo Sihombing (Jurnal Jaffray, 2022)
This article was written with the aim of analyzing a topic that is often the subject of discussion among Christians in general and theologians in particular. The topic to be analyzed is politics in the Old Testament as a biblical study. Through this article, we will seriously describe the views of Old Testament experts on politics and then see its relationship with Theopolitics as an important part offered in the Old Testament. In the end, this article will analyze and conclude comprehensively “what it really looks like” the Old Testament looked at politics and tried to relate it to the life of believers.